Epidermoid cyst complicating female genital mutilation and its psychological impact: A case report - Dejene, Tafese (Ethiopian Journal of Reproductive Health, 2021)
Abstract Epidermoid cysts are slowly growing tumors arising from invagination of the epidermis into the dermis traumatically or spontaneously. This implantation in the clitoris is most commonly induced by female genital mutilation. This is the case of epidermoid cyst of vulva reported in a 20 year old patient that caused significant worry and psychological disturbances on the patient.